Perioperative Management of Total Laryngectomy Patients: A Survey of American Head and Neck Society Surgeons. (June 2019) - Ahmed, Omar H.; Roden, Dylan F.; Ahmed, Yasmina C.; Wang, Binhuan; Nathan, Cherie-Ann O.; Myssiorek, David
Objectives: Standards of care for total laryngectomy (TL) patients in the postoperative period have not been established. Perioperative care remains highly variable and perhaps primarily anecdotally based. The aim of this study was to survey members of the American Head and Neck Society to capture management practices in the perioperative care of TL patients. Methods: In this survey study, an electronic survey was distributed to the international attending physician body of the American Head and Neck Society. Forty-five-question electronic surveys were distributed. A total of 777 members were invited to respond, of whom 177 (22.8%) fully completed the survey. The survey elicited information on management preferences in the perioperative care of TL patients. Differences in management on the basis of irradiation status and pharyngeal repair (primary closure vs regional or free flap reconstruction) were ascertained. Main outcomes and measures were time to initiate oral feeding, perioperative antibiotic selection and duration, and estimated pharyngocutaneous fistula rates. These measures were stratified by patient type. Results: Most respondents completed head and neck fellowships (77.0%) and practice at academic tertiary centers (72.3%). Ampicillin/sulbactam was the most preferred perioperative antibiotic (43.2%-49.1% depending on patient type), followed by cefazolin and metronidazole in combination (32.0%-33.7%) and then clindamycin (10.8%-12.6%). Compared with nonirradiated patients, irradiated patients were significantly more likely to have longer durations of antibiotics ( P < .05), longer postoperative times to initiate oral feeding ( P < .05), and higher estimated fistula rates ( P < .05). Additionally, in nonirradiated patients, flap-repaired patients (vs primary repair) were significantly more likely to have longer durations of antibiotics (odds ratio, 1.29; 95% confidence interval, 1.13-1.48) and postoperative times to initiate oral feeding (odds ratio, 2.24; 95% confidence interval, 1.76-2.84). Conclusions: Perioperative management of TL patients is highly variable. Management of antibiotics and oral feeding are significantly affected by irradiation status and scope of pharyngeal repair. Further studies are needed to standardize perioperative care for this unique patient population.